2005
DOI: 10.1002/jsfa.2375
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of ripening stages and climatic conditions on the physicochemical and sensorial parameters of two varieties of Vitis vinifera L. by principal component analysis: influence on enzymatic browning

Abstract: The present paper describes the effects of maturation on the physicochemical, biochemical and color components of Napoleon and Dominga grape varieties, and on any differences between them. Climatic conditions were taken into account to explain the results obtained. Protein levels increased during ripening and were correlated with pH. Polyphenoloxidase activity was affected by climatic conditions (rainfall) and increased to a greater degree in Dominga than in Napoleon. Taste tests were conducted to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…The statistical correlation between seasons for PPO activity during ripening is shown in Table 1, where statistically significant correlation between the 3 years studied is evident. This PPO activity is similar to that obtained by Serrano-Megías et al (2006) for table grapes in the Southeastern Spain but lower than that observed by Wissemann and Lee (1980) in wine grape varieties.…”
Section: Enzymatic Activity During Ripening Periodsupporting
confidence: 78%
See 3 more Smart Citations
“…The statistical correlation between seasons for PPO activity during ripening is shown in Table 1, where statistically significant correlation between the 3 years studied is evident. This PPO activity is similar to that obtained by Serrano-Megías et al (2006) for table grapes in the Southeastern Spain but lower than that observed by Wissemann and Lee (1980) in wine grape varieties.…”
Section: Enzymatic Activity During Ripening Periodsupporting
confidence: 78%
“…Since these factors are beyond human control, meteorological data during the growth and maturation periods must be taken into account to understand trends in PPO activity (Serrano-Megías et al, 2006). PPO activity of Dominga and Napoleon table grapes showed a maximum in the middle of ripening, coinciding with substantial rainfall (Serrano-Megías et al, 2006). The PPO of Crimson Seedless seemed to be less sensitive to weather conditions and no relationship between weather conditions and PPO activity was observed.…”
Section: Parametermentioning
confidence: 97%
See 2 more Smart Citations
“…(+)-catechin, (-)-epicatechin [13,21]. On the other hand, investigations on the concentration of polyphenolic antioxidants in grapes concern mostly the assay of grape berries during different stages of their maturation or when they have been injured by disease or UV irradiation [22,23]. There are only few reports on the antioxidant content of grapes produced under conditions similar to those of a commercial vineyard and mainly concern the determination of their resveratrol concentration.…”
Section: Introductionmentioning
confidence: 99%